A method for preparing a porous polyethylene implant

Through underwater granulation and sintering molding, porous polyethylene implants with larger pore sizes are prepared, which solves the problems of small pore sizes of the existing implants, resulting in infection and restricted tissue growth, and achieves better tissue Cell growth and implant stability.

CN119017728BActive Publication Date: 2025-02-21SHANGHAI POLLY MEDICAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411514789.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The average pore size of existing pores of porous polyethylene implants is small, which is prone to induce infection and limits the growth and vascularization of tissue cells.

Method used

By melt-extruding the polyethylene and performing underwater granulation, polyethylene particles with an average particle size of 300~800 μm were prepared, and sintered and molded in a mold and cooled to obtain a porous polyethylene implant.

Benefits of technology

The average pore size of porous polyethylene implants is significantly improved, promoting tissue cell growth, reducing infection risk, and improving implant stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119017728B_ABST
    Figure CN119017728B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of polymer materials, and in particular, relates to a method for preparing a porous polyethylene implant, comprising the following steps: a) melt-extrude polyethylene and then perform underwater granulation to obtain polyethylene particles with an average particle size of 300-800 μm; b) fill the polyethylene particles into a mold, sinter and form, and cool to obtain a porous polyethylene implant. The present invention first uses an underwater granulation process to prepare large polyethylene particles with a certain particle size, and then sinter these large polyethylene particles in a mold. During the sintering process, the large polyethylene particles contact and bond with each other to form abundant and large three-dimensional holes. The method of the present invention can be used to prepare a porous polyethylene implant with a larger pore size. The larger pore size can promote the growth of tissue cells, making the implant less likely to shift, and can also promote vascularization of the implant site and reduce the risk of infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a method for preparing a porous polyethylene implant. Background Art

[0002] Polyethylene is a polymer compound formed by the polymerization of ethylene monomers. It is generally categorized into low-density polyethylene (LDPE), high-density polyethylene (HDPE), and ultra-high molecular weight polyethylene (UHMWPE). Polyethylene has advantages such as toughness, abrasion resistance, chemical resistance, and good biosafety, leading to its widespread use in the medical field. Medical polyethylene is used in devices such as infusion tubing, blood transfusion bags, and artificial implants.

[0003] With polyethylene material as the matrix, a three-dimensional microporous structure can be formed inside it by regulating the molding process, so that it can combine the excellent comprehensive performance of polyethylene material with the advantages of porous material, greatly expanding the application field of polyethylene and achieving the goal of multifunctionality.

[0004] Compression molding-template leaching and sintering are two common methods for preparing porous polyethylene. The compression molding-template leaching method typically involves physically blending polyethylene powder with a porogen raw material in a specific ratio, adding the mixture to a mold, and then pressing it on a hot pressing machine. Finally, the porogen is removed to produce the porous polyethylene. However, this method often has the disadvantages of difficult pore parameter adjustment and porogen residues that can be harmful to the human body. The sintering method uses polyethylene powder as the raw material and subjects it to a certain temperature and pressure in a mold. The powders contact and bond to form sintering necks, and then rapidly cool the particles before they fully bond to retain the voids, ultimately forming a porous polyethylene with a three-dimensional porous structure. However, the polyethylene powder used in the sintering method is typically less than 100 μm in diameter, resulting in a small average pore size (approximately 20-50 μm) for the sintered porous polyethylene. This makes it susceptible to infection due to bacterial residues after implantation into the human body. Foreign scholars have reported that an average pore size of 100-250 μm in an implant is more conducive to tissue ingrowth and vascularization, reducing the risk of infection. A smaller pore size will limit the extent of tissue ingrowth and easily retain bacteria. A larger pore size will affect the long-term stability of the implant, and low cell adhesion efficiency is not conducive to cell proliferation. Domestic scholars have reported that a pore size greater than 100 μm is conducive to cell ingrowth, the delivery of nutrients, and the excretion of metabolic products. Other domestic scholars have reported the effect of porosity on cell adhesion and tissue growth. Too high a porosity is not conducive to cell adhesion and affects the long-term stability of the scaffold; too small a porosity will hinder the ingrowth of tissue cells. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing a porous polyethylene implant. The method provided by the present invention improves the process of preparing porous polyethylene by traditional sintering method, and greatly increases the average pore size of the sintered product.

[0006] The present invention provides a method for preparing a porous polyethylene implant, comprising the following steps:

[0007] a) melt-extruding the polyethylene and then underwater granulating it to obtain polyethylene particles with an average particle size of 300 to 800 μm;

[0008] b) filling the polyethylene particles into a mold, sintering and cooling to obtain a porous polyethylene implant.

[0009] Preferably, in step a), the polyethylene has a melt flow index of 0.5-50 g / 10 min under test conditions of 190° C. and 21.6 kg; and a weight average molecular weight of 150,000-1,500,000 g / mol.

[0010] Preferably, in step a), a plasticizer and / or a surfactant is added during the melting process.

[0011] Preferably, in step a), the plasticizer is one or more of PEG400, PEG2000 and PEG4000; and the surfactant is one or more of Span 40, Tween 40 and Tween 80.

[0012] Preferably, in step a), the plasticizer accounts for 0-5% of the total mass of polyethylene, plasticizer and surfactant; the surfactant accounts for 0-5% of the total mass of polyethylene, plasticizer and surfactant.

[0013] Preferably, in step a), the melt extrusion is carried out in a twin-screw extruder, the die opening diameter of the twin-screw extruder is 300-800 μm; the melt extruded melt is cut and granulated underwater, and the cutting machine speed is 300-1200 rpm.

[0014] Preferably, in step a), the screw speed of the twin-screw extruder is 100-300 rpm, and the barrel temperature is 180-220°C; and the water temperature for underwater cutting and granulation of the melt is 60-90°C.

[0015] Preferably, in step a), the polyethylene particles have a spheroidization degree of 40-100%.

[0016] Preferably, in step b), the sintering temperature is 140-220° C., and the sintering time is 3-15 minutes.

[0017] Preferably, the preparation method further comprises: performing functional modification on the porous polyethylene implant during the preparation process.

[0018] Preferably, the functional modification method includes sintering modification and / or surface modification.

[0019] Compared to the prior art, the present invention provides a method for preparing a porous polyethylene implant, comprising the following steps: a) melt-extruding polyethylene and then underwater granulating it to obtain polyethylene particles with an average particle size of 300-800 μm; b) filling the polyethylene particles into a mold, sintering them, and cooling them to obtain the porous polyethylene implant. The present invention first uses an underwater granulation process to prepare large polyethylene particles of a specific particle size. These large polyethylene particles are then sintered in a mold. During the sintering process, the large polyethylene particles contact and bond with each other, forming abundant and large three-dimensional pores. The present method can produce porous polyethylene implants with larger pores. The larger pore size promotes tissue cell ingrowth, making the implant less likely to dislodge, and promotes vascularization at the implant site, reducing the risk of infection. Furthermore, in the preferred technical solution provided by the present invention, the porous polyethylene implant can also be functionally modified to impart biological functions such as antibacterial and antioxidant properties, thereby further reducing the risk of infection and increasing the implant's service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0021] Figure 1 is a scanning electron microscope image of the nearly spherical UHWMPE microparticles prepared in Example 1 of the present invention;

[0022] Figure 2 This is a scanning electron microscope image of the porous polyethylene implant product prepared in Example 1 of the present invention;

[0023] Figure 3 This is a digital photograph of a porous polyethylene implant product containing a functional additive coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0025] The present invention provides a method for preparing a porous polyethylene implant, comprising the following steps:

[0026] a) melt-extruding the polyethylene and then underwater granulating it to obtain polyethylene particles with an average particle size of 300 to 800 μm;

[0027] b) filling the polyethylene particles into a mold, sintering and cooling to obtain a porous polyethylene implant.

[0028] In the preparation method provided by the present invention, in step a), in order to granulate the spherical microparticles mentioned in the present invention, it is necessary to keep the melt flow index of the polyethylene within a certain range as much as possible. When the melt flow index is too low, the particles obtained by shaping are not easy to form a sphere, but are easy to form a cylindrical shape. According to the stacking theory, the porosity of spherical particles during stacking and sintering will be higher than that of cylindrical particles. When the melt flow index is too high, although microparticles with good sphericity can be produced, the fluidity is too good, and the particles are prone to excessive fusion during the sintering process, resulting in a decrease in porosity. In the present invention, the melt flow index of the polyethylene is preferably 0.5~50g / 10min (190℃, 21.6kg), more preferably 2~40g / 10min, more preferably 5~35g / 10min, and most preferably 10~30g / 10min. The polyethylene with the optimized melt flow index has improved melt fluidity, a higher degree of spheroidization after granulation, and is less likely to undergo excessive fusion between particles during sintering. In the present invention, the melt flow index of the polyethylene can be specifically 0.5 g / 10 min, 1 g / 10 min, 2 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min or 50 g / 10 min.

[0029] In the preparation method provided by the present invention, in step a), although the molecular weight of the polyethylene generally does not directly affect the porosity of the product, the molecular weight is negatively correlated with the melt flow index (the larger the molecular weight, the smaller the melt index). Therefore, in order to granulate the spherical microparticles mentioned in the present invention, the molecular weight of the polyethylene also needs to be controlled within a certain range. In the present invention, the weight average molecular weight of the polyethylene is preferably 150,000 to 1,500,000 g / mol, more preferably 180,000 to 1,100,000 g / mol, further preferably 200,000 to 700,000 g / mol, and most preferably 250,000 to 400,000 g / mol. The polyethylene with the optimized weight average molecular weight has improved melt flowability, a higher degree of spheroidization after granulation, and is less likely to cause excessive fusion between particles during sintering. In the present invention, the weight average molecular weight of the polyethylene can be specifically 150000 g / mol, 200000 g / mol, 250000 g / mol, 300000 g / mol, 350000 g / mol, 400000 g / mol, 450000 g / mol, 500000 g / mol, 550000 g / mol, 600000 g / mol, 650000 g / mol l, 700000g / mol, 750000g / mol, 800000g / mol, 850000g / mol, 900000g / mol, 950000g / mol, 10 00000g / mol, 1100000g / mol, 1200000g / mol, 1300000g / mol, 1400000g / mol or 1500000g / mol.

[0030] In the preparation method provided herein, in step a), a plasticizer and / or surfactant may optionally be added during the melting process. The addition of surfactants and plasticizers is intended to enhance the fluidity of the polyethylene, thereby producing microparticles with improved sphericity, thereby improving the pore morphology uniformity, average pore size, and porosity of the final product. It should be noted that the addition of these two components is not mandatory. If a high melt index polyethylene within a certain range is selected, microparticles with good sphericity can be produced even without these components by adjusting equipment parameters.

[0031] In the preparation method provided by the present invention, in step a), the plasticizer includes but is not limited to one or more of PEG400, PEG2000 and PEG4000. These types of plasticizers have good biosafety. In the present invention, the plasticizer preferably accounts for 0-5% of the total mass of polyethylene, plasticizer and surfactant (if it exceeds 5%, the biosafety may not meet the requirements), more preferably 0.5-4.5%, more preferably 1-4%, and most preferably 1.5-3.5%. After the plasticizer is added in an optimal amount, the polyethylene has better fluidity during melt extrusion, better biosafety, and less risk after implantation into the human body. In the present invention, the plasticizer can specifically account for 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of the total mass of polyethylene, plasticizer and surfactant.

[0032] In the preparation method provided by the present invention, in step a), the surfactant includes but is not limited to one or more of Span 40, Tween 40, and Tween 80; the surfactant preferably accounts for 0-5% of the total mass of the polyethylene, plasticizer, and surfactant (if it exceeds 5%, the biosafety may not meet the requirements), more preferably 0.5-4.5%, more preferably 1-4%, and most preferably 1.5-3.5%. After the surfactant is added in the optimal amount, the polyethylene has better fluidity during melt extrusion and better biosafety, and has lower risks after implantation into the human body. In the present invention, the surfactant can specifically account for 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% of the total mass of the polyethylene, plasticizer, and surfactant.

[0033] In the preparation method provided by the present invention, in step a), the melt extrusion is carried out in a twin-screw extruder; wherein, the screw speed of the twin-screw extruder is preferably 100-300 rpm, specifically 100 rpm, 150 rpm, 200 rpm, 250 rpm or 300 rpm; the barrel temperature of the twin-screw extruder is preferably 180-220°C, specifically, the temperature of the rear section (near the feed port) is preferably 180-200°C, specifically 180°C, 190°C or 200°C, the temperature of the middle section is preferably 190-210°C, specifically 190°C, 200°C or 210°C, and the temperature of the front section (near the discharge port) is preferably 200-220°C, specifically 200°C, 210°C or 220°C. In the present invention, the die opening diameter of the twin-screw extruder is preferably 300-800 μm, more preferably 400-700 μm, and even more preferably 450 μm-650 μm. After the die opening diameter is optimized, the size range of the polyethylene particles after granulation is more suitable; the die opening diameter of the twin-screw extruder can specifically be 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm or 800 μm.

[0034] In the preparation method provided by the present invention, in step a), the melt-extruded melt is cut and granulated underwater; wherein, the cutter speed is preferably 300-1200 rpm, more preferably 400-1100 rpm, preferably 500-1000 rpm, and most preferably 600-900 rpm. The preferred cutter speed can match the preferred die opening diameter, and the polyethylene particles obtained by granulation have better spheroidization; the cutter speed can specifically be 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, 1000 rpm, 1100 rpm or 1200 rpm. In the present invention, the water temperature for underwater cutting and granulation of the melt is preferably 60-90°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C.

[0035] In the preparation method provided herein, in step a), the average particle size of the polyethylene particles is preferably 300-800 μm, more preferably 350-750 μm, even more preferably 400-700 μm, and most preferably 450-650 μm. The optimized average particle size of the polyethylene particles results in a more suitable pore size for the implant obtained after sintering. In the present invention, the average particle size of the polyethylene particles can specifically be 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, or 800 μm.

[0036] In the preparation method provided by the present invention, in step a), the polyethylene particles are spherical or nearly spherical, and their degree of sphericity is preferably 40% to 100%, more preferably 50% to 100%, even more preferably 60% to 100%, and most preferably 80% to 100%. Polyethylene particles with a preferred degree of sphericity have more uniform pore size and porosity after sintering. In the present invention, the degree of sphericity of the polyethylene particles can specifically be 40%, 44%, 45%, 50%, 54%, 55%, 60%, 65%, 70%, 71%, 74%, 75%, 78%, 80%, 85%, 90%, 93%, 95%, or 100%.

[0037] In the preparation method provided by the present invention, in step a), the spheroidization degree is defined as the ratio of the particle's circumference equivalent diameter to the particle's area equivalent diameter, which can be described by the following formula: Q = d1 / d a , where d1 represents the equivalent diameter of the particle's perimeter. If the particle's perimeter is l, then l=2πd1; d a Represents the area equivalent diameter of the particle. If the area of ​​the particle is A, then A=πd a Spheroidization is measured by selecting a scanning electron microscope image (the selected area should contain at least five particles) and importing it into Image-Pro PLUS software. Using the software's calculation function, the ratio of the particle perimeter equivalent diameter to the particle area equivalent diameter is calculated. The closer this equivalent diameter ratio is to 1, the higher the spheroidization. The higher the spheroidization, the more likely the packing contact between particles is to be point contact, resulting in more uniform pores.

[0038] In the preparation method provided by the present invention, in step b), the temperature and time of the sintering molding should be appropriately adjusted according to the melt index. If the sintering temperature is low, the fusion effect between the particles is poor, the porosity is large, but the mechanical strength is insufficient; if the sintering temperature is high, the fusion effect between the particles is good, the porosity is low, but the mechanical strength will be high; at the same temperature, the longer the sintering time, the better the particle fusion and the smaller the porosity.

[0039] In the preparation method provided by the present invention, in step b), the sintering temperature is preferably 140-220°C, more preferably 150-210°C, more preferably 160-200°C, and most preferably 170-190°C. After the sintering temperature is optimized, the pore size and porosity of the implant are more suitable. In the present invention, the sintering temperature can specifically be 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, or 220°C.

[0040] In the preparation method provided herein, in step b), the sintering time is preferably 3 to 15 minutes, more preferably 5 to 13 minutes, even more preferably 6 to 12 minutes, and most preferably 7 to 11 minutes. The optimized sintering time results in a more suitable pore size and porosity for the implant. In the present invention, the sintering time can specifically be 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, or 15 minutes.

[0041] In the preparation method provided by the present invention, in step b), the sintering molding equipment includes but is not limited to a vacuum drying oven, an electric heating tablet press or a flat vulcanizing press. The equipment is preferably preheated before use. The preheating temperature is preferably 100-150°C, more preferably 120°C, and the preheating time is preferably 20-40 minutes, more preferably 30 minutes.

[0042] The preparation method provided herein preferably further comprises: performing functional modification on the porous polyethylene implant during its preparation. In the present invention, such functional modification includes, but is not limited to, enhancing hydrophilicity to promote tissue growth and accelerate postoperative recovery; enhancing antibacterial capacity to prevent short-term postoperative infection; and enhancing antioxidant capacity to improve the long-term stability of the implant.

[0043] In the preparation method provided by the present invention, the functional modification method preferably includes sintering modification and / or surface modification. Among them, the sintering modification refers to mixing the functional additives with polyethylene particles obtained by underwater granulation in a certain proportion, adding them together to a mold for sintering molding; or immersing the finished porous polyethylene implant in a solution containing a certain proportion of functional additives, taking it out and then sintering it; or directly adding the functional additives to the finished porous polyethylene implant, shaking it evenly and then sintering it, so that the functional additives will melt and sinter into the pores of the porous polyethylene; functional additives that can be used for sintering modification include but are not limited to one or more mixtures of nano-gold, nano-silver, nano-copper, nano-zinc oxide, nano-gallium oxide and bioglass. The surface modification method includes but is not limited to plasma treatment, acidification treatment or sandblasting treatment, the main purpose of which is to improve the roughness, surface energy and hydrophilicity of the sample surface, and then immerse the surface-treated porous polyethylene in a polydopamine solution containing an antibacterial agent and / or an antioxidant to obtain a porous polyethylene containing a functional coating; the antibacterial agent includes but is not limited to one or more of triclosan, chitosan and antimicrobial peptides; the antioxidant includes but is not limited to one or more of vitamin E, tea polyphenols, proanthocyanidins and resveratrol.

[0044] In the preparation method provided by the present invention, when performing the sintering modification, the added amount of the functional additive is preferably 1~5wt% of the mass of the porous polyethylene implant; when performing the surface modification, the added amount of the antibacterial agent and the antioxidant is independently preferably 5~15wt% of the mass of the porous polyethylene implant.

[0045] In the preparation method provided by the present invention, the average pore size of the prepared porous polyethylene implant can be controllably adjusted within 30~300μm. At the same time, a porous polyethylene implant with a larger pore size can be prepared, so that its average pore size is preferably 60~300μm, more preferably 80~280μm, more preferably 100~260μm, and most preferably 120~240μm. A larger pore size is more suitable for cell and tissue growth, the tissue compatibility of the implant is improved, and immune rejection reaction is less likely to occur. A pore size that is too small is not conducive to cell growth and the delivery of nutrients and the excretion of metabolic products. It is also easy for macrophages to be unable to grow into the pores and phagocytize residual bacteria, causing infection. A pore size that is too large will affect the long-term stability of the implant, and the low cell adhesion efficiency is not conducive to cell proliferation. In the present invention, the average pore size of the porous polyethylene implant can be specifically 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm or 300μm.

[0046] In the preparation method provided by the present invention, the porosity of the porous polyethylene implant obtained is preferably 20-60%, more preferably 30-60%, further preferably 35-60%, and most preferably 40-60%. The preferred porosity can maintain appropriate mechanical strength while allowing an appropriate amount of tissue to grow in, thereby promoting the stability of the implant. Too high a porosity is not conducive to cell adhesion, and the long-term stability of the implant will be affected, making the implant structure prone to damage; too low a porosity will hinder the ingrowth of tissue cells. In the present invention, the porosity of the porous polyethylene implant can be specifically 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 60%.

[0047] The preparation method provided by the present invention first adopts an underwater granulation process to prepare large polyethylene particles with a certain particle size, and then sintering these large polyethylene particles in a mold. During the sintering process, the large polyethylene particles contact and bond with each other to form abundant and large three-dimensional holes. The method of the present invention can be used to prepare a porous polyethylene implant with a larger pore size. The larger pore size can promote the growth of tissue cells, making the implant less likely to shift, and can also promote the vascularization of the implant site, reducing the risk of infection. In addition, in the preferred technical solution provided by the present invention, the porous polyethylene implant can also be functionally modified to give it biological functions such as antibacterial and antioxidant properties, thereby further reducing the infection risk of the implant and increasing the service life of the implant.

[0048] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples.

[0049] Example 1

[0050] A commercially available implantable grade UHMWPE powder with a weight-average molecular weight of 1,500,000 g / mol and a melt flow index of 0.5 g / 10 min (190°C, 21.6 kg) was selected. The UHMWPE powder, PEG2000, and Tween 80 were added to the twin-screw extruder of the underwater granulation system at a mass ratio of 90:5:5. The extruder parameters were adjusted as follows: screw speed 150 rpm, barrel rear section temperature 190°C, middle section temperature 200°C, front section temperature 210°C, die opening diameter 500 μm, cutter speed 700 rpm, and circulating water temperature 80°C. After underwater granulation, nearly spherical UHMWPE microparticles with an average particle size of 500 μm were obtained, with an average spheroidization degree of 81%. The micromorphology is as follows: Figure 1 shown.

[0051] Weigh 10g of the above UHMWPE microparticles and pour them into the lower mold and flatten them, then cover them with an aluminum upper mold. Place the entire mold set on an electric heating tablet press preheated at 120℃ for 30min, ensuring that the upper mold and the upper mold of the tablet press have no pressure contact. Set the parameters: the holding section temperature is 180℃, and the holding section time is 10min. After the holding sintering is completed, water cool to room temperature to obtain a porous polyethylene implant product with a microscopic morphology as shown below. Figure 2 The pore parameters of the product were tested using a mercury intrusion instrument, and the average pore diameter of the product was 190μm and the porosity was 52%.

[0052] The porous polyethylene implant product was added to 10 mol / L concentrated sulfuric acid for acidification for 15 min, taken out and ultrasonically cleaned, then added to a polydopamine solution containing 10 wt% chitosan and 5 wt% vitamin E, stirred at room temperature for 48 h, taken out and ultrasonically cleaned and dried in sequence to obtain a porous polyethylene implant product containing a functional additive coating. The product appearance is as follows: Figure 3shown.

[0053] Example 2

[0054] On the basis of Example 1, other process parameters were not adjusted, the die opening diameter was adjusted to 800 μm, and the cutting machine speed was adjusted to 300 rpm, to obtain nearly spherical UHMWPE microparticles with an average particle size of 800 μm and an average spheroidization degree of 78%.

[0055] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 250 μm and a porosity of 58%.

[0056] Example 3

[0057] On the basis of Example 1, other process parameters were not adjusted, the die opening diameter was adjusted to 300 μm, and the cutting machine speed was adjusted to 1200 rpm, to obtain nearly spherical UHMWPE microparticles with an average particle size of 300 μm and an average spheroidization degree of 75%.

[0058] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 100 μm and a porosity of 30%.

[0059] Example 4

[0060] On the basis of Example 1, other process parameters were not adjusted, and the cutting machine speed was adjusted to 500 rpm, to obtain nearly spherical UHMWPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 57%.

[0061] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 170 μm and a porosity of 38%.

[0062] Example 5

[0063] On the basis of Example 1, other process parameters were not adjusted, and the cutting machine speed was adjusted to 300 rpm, to obtain nearly spherical UHMWPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 44%.

[0064] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 150 μm and a porosity of 31%.

[0065] Example 6

[0066] On the basis of Example 1, other process parameters were not adjusted, and the cutting machine speed was adjusted to 1000 rpm to obtain ellipsoidal UHMWPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 61%.

[0067] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 180 μm and a porosity of 40%.

[0068] Example 7

[0069] On the basis of Example 1, other process parameters were not adjusted, and the cutting machine speed was adjusted to 1200 rpm to obtain ellipsoidal UHMWPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 52%.

[0070] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 150 μm and a porosity of 35%.

[0071] Example 8

[0072] On the basis of Example 1, other process parameters were not adjusted, and the die opening diameter was adjusted to 300 μm to obtain ellipsoidal UHMWPE microparticles with an average particle size of 300 μm and an average spheroidization degree of 62%.

[0073] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 90 μm and a porosity of 28%.

[0074] Example 9

[0075] On the basis of Example 1, other process parameters were not adjusted, and the die opening diameter was adjusted to 800 μm to obtain ellipsoidal UHMWPE microparticles with an average particle size of 800 μm and an average spheroidization degree of 58%.

[0076] The UHMWPE microparticles were sintered according to the method and conditions of Example 1 to obtain a porous polyethylene implant product with an average pore diameter of 220 μm and a porosity of 47%.

[0077] Example 10

[0078] A commercially available implant-grade HDPE powder with a weight-average molecular weight of 250,000 g / mol and a melt flow index of 30 g / 10 min (190°C, 21.6 kg) was used. This HDPE powder, along with PEG 2000 and Tween 80 at a mass ratio of 95:2.5:2.5, was added to a twin-screw extruder in an underwater pelletizing system. Extruder parameters were adjusted to: screw speed 200 rpm, barrel temperature 190°C, mid-section temperature 200°C, and front-section temperature 210°C, die opening diameter 500 μm, cutter speed 500 rpm, and circulating water temperature 80°C. After underwater pelletization, nearly spherical HDPE microparticles with an average particle size of 500 μm and an average degree of spheroidization of 90% were obtained.

[0079] Weigh 10g of the above-mentioned HDPE microparticles and 0.2g of medical nanosilver particles, mix them evenly, pour them into the lower mold and flatten them, and cover them with an aluminum upper mold. Place the entire set of molds on an electric heating tablet press preheated at 120°C for 30 minutes to ensure that the upper mold and the upper mold of the tablet press are in non-pressure contact. Set the parameters: the holding section temperature is 180°C, and the holding section time is 5 minutes. After the insulation sintering is completed, water cool to room temperature to obtain a porous polyethylene implant product. The product is tested for pore parameters using a mercury intrusion instrument. The average pore size of the product is 200μm and the porosity is 47%.

[0080] Example 11

[0081] Based on Example 10, other process parameters were not adjusted. A commercially available implant-grade HDPE powder was selected, having a weight-average molecular weight of 400,000 g / mol and a melt flow index of 10 g / 10 min (190°C, 21.6 kg). Through an underwater granulation process, cylindrical HDPE microparticles with an average particle size of 500 μm and an average degree of spheroidization of 54% were obtained.

[0082] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore diameter of 90 μm and a porosity of 31%.

[0083] Example 12

[0084] Based on Example 10, other process parameters were not adjusted. A commercially available implant-grade HDPE powder was selected with a weight-average molecular weight of 150,000 g / mol and a melt flow index of 50 g / 10 min (190°C, 21.6 kg). Through an underwater granulation process, nearly spherical HDPE microparticles with an average particle size of 500 μm and an average degree of spheroidization of 93% were obtained.

[0085] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore diameter of 40 μm and a porosity of 26%.

[0086] Example 13

[0087] On the basis of Example 10, other process parameters were not adjusted, and the holding time of the tablet press was set to 10 minutes to obtain a porous polyethylene implant product with an average pore diameter of 140 μm and a porosity of 36%.

[0088] Example 14

[0089] On the basis of Example 10, other process parameters were not adjusted, and the holding time of the tablet press was set to 3 minutes to obtain a porous polyethylene implant product with an average pore diameter of 220 μm and a porosity of 49%.

[0090] Example 15

[0091] On the basis of Example 10, other process parameters were not adjusted, and the temperature of the holding section of the tablet press was set to 220° C. to obtain a porous polyethylene implant product with an average pore diameter of 80 μm and a porosity of 28%.

[0092] Example 16

[0093] On the basis of Example 10, other process parameters were not adjusted, and the temperature of the holding section of the tablet press was set to 140° C. to obtain a porous polyethylene implant product with an average pore diameter of 260 μm and a porosity of 58%.

[0094] Example 17

[0095] Based on Example 10, HDPE powder, PEG2000, and Tween 80 were added to a twin-screw extruder of an underwater pelletizing system in a mass ratio of 100:0:0, and other processes were not adjusted to obtain nearly spherical HDPE microparticles with an average particle size of 500 μm and an average degree of spheroidization of 78%.

[0096] Example 18

[0097] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore diameter of 170 μm and a porosity of 43%.

[0098] Based on Example 10, HDPE powder, PEG2000, and Tween 80 were added to a twin-screw extruder of an underwater pelletizing system in a mass ratio of 90:5:5, and other processes were not adjusted to obtain nearly spherical HDPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 96%.

[0099] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore size of 220 μm and a porosity of 54%.

[0100] Example 19

[0101] Based on Example 10, HDPE powder, PEG2000, and Tween 80 were added to a twin-screw extruder of an underwater pelletizing system in a mass ratio of 95:1:4. Other processes were not adjusted to obtain nearly spherical HDPE microparticles with an average particle size of 500 μm and an average degree of spheroidization of 77%.

[0102] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore size of 220 μm and a porosity of 52%.

[0103] Example 20

[0104] Based on Example 10, HDPE powder, PEG2000, and Tween 80 were added to the twin-screw extruder of the underwater pelletizing system in a mass ratio of 95:4:1. Other processes were not adjusted to obtain nearly spherical HDPE microparticles with an average particle size of 500 μm and an average spheroidization degree of 78%.

[0105] The HDPE microparticles were sintered according to the method and conditions of Example 10 to obtain a porous polyethylene implant product with an average pore size of 220 μm and a porosity of 53%.

[0106] Through Examples 1, 4 to 7, it can be seen that under the same conditions, as the cutting speed increases, the degree of spheroidization first increases and then decreases, and the average pore size and porosity of the porous polyethylene implant product finally prepared also first increase and then decrease. The degree of spheroidization can be controlled as needed to adjust the uniformity of its pore size, and the average pore size and porosity of the prepared porous polyethylene implant product can be further adjusted and controlled.

[0107] From Examples 1, 9, and 10, it can be seen that, under the same conditions, as the die opening diameter increases, the average pore diameter increases accordingly.

[0108] Examples 10, 17, and 18 demonstrate that, under identical conditions, increasing the amount of PEG 2000 and Tween 80 leads to a gradual increase in the degree of spheroidization, and the average pore size and porosity of the resulting porous polyethylene implant product also gradually increase. Increasing the amount of surfactant and plasticizer can improve the degree of spheroidization and regulate the average pore size and porosity of the resulting porous polyethylene implant product.

[0109] Through Examples 10, 19, and 20, it can be seen that under the same conditions, when the total mass ratio of the surfactant and the plasticizer remains unchanged, the ratio of the surfactant and the plasticizer changes, and there is no significant difference in the spheroidization degree, and there is no significant difference in the average pore size and porosity of the porous polyethylene implant products.

[0110] Examples 10-12 show that, under the same conditions, as the molecular weight increases, the degree of spheroidization gradually decreases, and the average pore size and porosity of the porous polyethylene implant product produced gradually increase. By adjusting the molecular weight of the polyethylene used, the degree of spheroidization can be adjusted and controlled, and the average pore size and porosity of the porous polyethylene implant product produced can be adjusted and controlled.

[0111] Examples 10, 13, and 14 show that, under identical conditions, increasing the tablet press hold time gradually decreases the average pore size and porosity of the porous polyethylene implant product. Adjusting the tablet press hold time can adjust the average pore size and porosity of the porous polyethylene implant product.

[0112] Examples 10, 15, and 16 show that, under identical conditions, as the tablet press holding section temperature increases and the holding time remains constant, the average pore size and porosity of the porous polyethylene implant product produced gradually decrease. By adjusting the tablet press holding temperature, the average pore size and porosity of the porous polyethylene implant product can be adjusted and controlled.

[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous polyethylene implant, characterized in that: The following steps are involved: a) melt-extrude the polyethylene and then perform underwater granulation to obtain polyethylene particles with an average particle size of 300-800 μm; In step a), the melt extrusion is carried out in a twin-screw extruder, the die opening diameter of the twin-screw extruder is 300-800 μm; the melt extruded melt is cut and granulated underwater, and the cutting machine speed is 300-1200 rpm; In step a), the spheroidization degree of the polyethylene particles is 40-100%; b) filling the polyethylene particles into a mold, sintering and cooling to obtain a porous polyethylene implant; In step b), the sintering temperature is 140-220° C. and the sintering time is 3-15 min.

2. The preparation method according to claim 1, characterized in that: In step a), the polyethylene has a melt flow index of 0.5-50 g / 10 min under test conditions of 190° C. and 21.6 kg; and a weight average molecular weight of 150,000-1,500,000 g / mol.

3. The preparation method according to claim 1, characterized in that: In step a), a plasticizer and / or a surfactant is also added during the melting process.

4. The preparation method according to claim 3, characterized in that: In step a), the plasticizer is one or more of PEG400, PEG2000 and PEG4000; the surfactant is one or more of Span 40, Tween 40 and Tween 80.

5. The preparation method according to claim 3, characterized in that: In step a), the plasticizer accounts for 0-5% of the total mass of polyethylene, plasticizer and surfactant; the surfactant accounts for 0-5% of the total mass of polyethylene, plasticizer and surfactant.

6. The preparation method according to claim 1, characterized in that: In step a), the screw speed of the twin-screw extruder is 100-300 rpm, and the barrel temperature is 180-220° C.; the water temperature of the melt during underwater cutting and granulation is 60-90° C.

7. The preparation method according to claim 1, characterized in that: Also includes: During the preparation of the porous polyethylene implant, it is functionally modified.

8. The preparation method according to claim 7, characterized in that: The functional modification methods include sintering modification and / or surface modification.

Citation Information

Patent Citations

  • Manufacturing method of artificial sclerite shaping implant with polyvinyl plastics

    CN101161294A

  • Medical implant or medical implant part comprising porous UHMWPE and process for producing the same

    US20050065307A1